PO198 The value of patient and public involvement in research in motor neurone disease. (1st December 2017) - Hobson, Esther; Musson, Lucy; McDermott, Christopher
Abstract : The Sheffield Motor Neurone Disease Research Advisory Group (SMNDRAG) was established in 2009 to enable those with an experience of living with MND to improve the way research is conducted. Patient and Public Involvement is a relatively recent initiative: there are many areas of uncertainty, such as how best to collaborate with these volunteers. We explored participants' experiences of the SMNDRAG, the barriers and enablers to participation, the experiences of clinicians and scientists who collaborate with the SMNDRAG and the impact that the group has had on research. We conducted 13 semi-structured interviews and used thematic analysis to identify relevant themes. We identified many examples of where the SMNDRAG had had a positive impact on research. This included the Sheffield neck collar project in which the SMNDRAG played a major role at every stage. The group had identified the need to improve neck collars and was involved in the development, evaluation and dissemination of the collar. The sense of ownership felt by the members fostered by the collaboration was a key contributor to the success of the research. We offer an insight into how to harness the perspectives of those with a lived experience of a disease to improve research.